Pengaruh Konsentrasi Rebusan Kelopak Bunga Rossella terhadap pH Saliva Buatan - Prasetyo Adi; Ambar Puspitasari; Murni Ukhuwah I (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
The Effect of Rossella Flower Petals Stew to Artificial Saliva pH. Saliva is a complex oral fluids. One of the microorganisms that cause the saliva’s pH becomes acid is Streptococcus mutans. Water stew of Rossella flower petals (Habiscus sabdariffa L) contains flavonoids and anthocyanins that interfere metabolism of the cells and growth of Streptococcus mutans. The purpose of this experimental was to know the effect of water stew Rossella flower petals concentration in pH scale and absorbance score of artificial saliva which induced with Streptococcus mutans by in vitro. The method which applied here was True Experimental Design, post test control group design. The concentrations that used in this study were 5%, 15%, 25% and 35%. The results described the differences in pH scale and absorbance score of artificial saliva which induced with Streptococcus mutans between treatment group (added by water stew Rossella petals) and control group. Data analysis using correlation and regression test showed the effect of water stew of Rossella flower petals in pH scale of artificial saliva was 99.2%. The conclusion of this experimental explained the increase of pH scale after added with the water stew of Rossella flower petals, also showed a significant differences of pH scale of artificial saliva between treatment group and control group based on the One-Way ANOVA test, and the water stew of Rossella flower petals was effective to maintain pH scale of artificial saliva approach normal pH scale